Business rule engines and AI for Excel Power users : capture and scale your business knowledge into the cloud - with Microsoft Office and the Red Hat Business Rules engine /: capture and scale your business knowledge into the cloud - with Microsoft Office and the Red Hat Business Rules engine. (2023) - Browne, Paul
No abstract available